BMP9 counteracts the tumorigenic and pro-angiogenic potential of glioblastoma. Issue 10 (November 2018) - Porcù, Elena; Maule, Francesca; Boso, Daniele; Rampazzo, Elena; Barbieri, Vito; Zuccolotto, Gaia; Rosato, Antonio; Frasson, Chiara; Viola, Giampietro; Della Puppa, Alessandro; Basso, Giuseppe; Persano, Luca
Abstract Glioblastoma multiforme (GBM) is a highly vascularized and aggressive brain tumor, with a strong ability to disseminate and invade the surrounding parenchyma. In addition, a subpopulation of GBM stem cells has been reported to possess the ability to transdifferentiate into tumor-derived endothelial cells (TDECs), supporting the resistance to anti-angiogenic treatments of newly formed blood vessels. Bone Morphogenetic Protein 9 (BMP9) is critically involved in the processes of cancer cell differentiation, invasion and metastasis, representing a potential tool in order to impair the intrinsic GBM aggressiveness. Here we demonstrate that BMP9 is able to trigger the activation of SMADs in patient-derived GBM cells, and to strongly inhibit proliferation and invasion by reducing the activation of PI3K/AKT/MAPK and RhoA/Cofilin pathways, respectively. Intriguingly, BMP9 treatment is sufficient to induce a strong differentiation of GBM stem-like cells and to significantly counteract the already reported process of GBM cell transdifferentiation into TDECs not only in in vitro mimicked TDEC models, but also in vivo in orthotopic xenografts in mice. Additionally, we describe a strong BMP9-mediated inhibition of the whole angiogenic process engaged during GBM tumor formation. Based on these results, we believe that BMP9, by acting at multiple levels against GBM cell aggressiveness, can be considered a promising candidate, to be further developed, for the future therapeutic management of GBM.